Propuesta de un procedimiento para obtener el protocologo técnico de almacenamiento para harina de pescado ensacada otorgado por el organismo nacional de sanidad pesquera (sanipes) - Mostacero Saldaña, Elmo David (2015)
The aim of this work was to develop a process in which the steps and the steps to take to obtain the Technical Protocol Storage Fishmeal bagged awarded by the Organismo Nacional de Sanidad Pesquera (SANIPES) is defined. To obtain the next job will be started after the submission of documentation to table parts of the Technological Institute of Production and culminates with the issuance of the Technical Protocol Storage granted by SANIPES and for this we had to collect all the information both in documentation and field work, it having all the information is analyzed and designed the procedure, resulting in the following: Presentation of documentation Document Processing ITP, with the documentary approval comes negotiations with decentralized Branch (FD) of the ITP in which the date of the audit is coordinated by the audit inspector FD is he who assesses the conditions of storage and control programs product if any observations that attempt against the safety of the product that gives the no provision of the service, the administrator of the company has 10 days to request a reinspection and a period equal or higher to the re inspection issued by the Fisheries Nationwide Health Authority (ASPNN) if warranted; in the absence of observations that threaten the safety of the product with the Technical Protocol Storage Fishmeal it is issued.